Pengaruh Pelayanan Terpadu Satu Pintu Terhadap Citra Kantor Wilayah Kementerian Agama Provinsi Jambi - Tuti Alfiani; Ansusa Putra; Agus Selamet Nugroho (MAUIZOH: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
The image of the agency is an important thing because it can make an agency good or even bad. One Stop Integrated Service (PTSP) Regional Office of the Ministry of Religion of Jambi Province is one of the drivers to get a good image in the community. This study aims to determine the effect of excellent service at PTSP on the image of the Regional Office of the Ministry of Religion of Jambi Province. This research is a qualitative research with data collection through interviews with the research subjects, namely the person in charge of PTSP, PTSP officers, employees of the Regional Office of the Ministry of Religion of Jambi Province. The results showed that: in improving the image of the Regional Office of the Ministry of Religion of Jambi Province, PTSP provided excellent services such as providing satisfaction to customers, providing friendly, fast and easy service; Responsible; Good service mechanisms and procedures; clarity in administrative costs; Factors that support improving the image of the Regional Office of the Ministry of Religion of Jambi Province in terms of excellent service at PTSP are the form of services provided to the community and, the facilities and infrastructure provided are very supportive of the service, while the inhibiting factor is the lack of competent human resources in PTSP, and there are still many It is the people who do not know the service administration system provided, especially the online administration system.